MEMBANGUN LINGKUNGAN KERJA HARMONIS DAN KONDUSIF: KAJIAN PUSTAKA UNTUK MENINGKATKAN PRODUKTIVITAS DAN KEPUASAN KARYAWAN - Hari Setiawan; Al-Amin (CV. Adiba Aisha Amira, 2025)
This study aims to comprehensively review previous theories and research findings on the development of a harmonious and conducive work environment and its impact on employee productivity and satisfaction. The literature review was conducted by examining various aspects of the work environment, both physical and psychological, that support the creation of a comfortable, safe, and inclusive work atmosphere. The findings show that a harmonious work environment, which includes open communication, good interpersonal relationships, performance recognition, and work-life balance, contributes significantly to increasing employee motivation, engagement, and productivity. In addition, employee job satisfaction increases when their psychological and physical needs are met in the work environment. This study recommends that organisations consistently manage and improve the quality of their work environment as an effective strategy for achieving optimal performance and sustainable job satisfaction.